2014
DOI: 10.1097/dad.0000000000000035
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Mucosal Melanoma

Abstract: Head and neck mucosal melanoma (MM) is an aggressive and rare neoplasm of melanocytic origin. To date, few retrospective series and case reports have been reported on MM. This article reviews the current evidence on head and neck MM and the molecular pathways that mediate the pathogenesis of this disease. Head and neck MM accounts for 0.7%-3.8% of all melanomas and involve (in decreasing order of frequency) the sinonasal cavity, oral cavity, pharynx, larynx, and upper esophagus. Although many studies have exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
86
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 75 publications
0
86
1
2
Order By: Relevance
“…For example, 66% of patients with mucosal melanoma arising on the larynx or pharynx report a history of smoking, and anorectal melanoma appears to be more common in patients with HIV. 16,64 CONCLUSION In summary, our review of the literature suggests important clinical and histological similarities between acral and mucosal melanomas. Whereas cutaneous melanomas may be somewhat common in women before the age of 50, sun-protected subtypes are rarely diagnosed before the seventh and eighth decades of life.…”
Section: Inherited and Other Risk Factorsmentioning
confidence: 99%
“…For example, 66% of patients with mucosal melanoma arising on the larynx or pharynx report a history of smoking, and anorectal melanoma appears to be more common in patients with HIV. 16,64 CONCLUSION In summary, our review of the literature suggests important clinical and histological similarities between acral and mucosal melanomas. Whereas cutaneous melanomas may be somewhat common in women before the age of 50, sun-protected subtypes are rarely diagnosed before the seventh and eighth decades of life.…”
Section: Inherited and Other Risk Factorsmentioning
confidence: 99%
“…Many foreign studies with small sample sizes (161)(162)(163) found that the BRAF gene mutation rate was 0−10% in MM patients, KIT gene mutation rate was 5−27%, and NRAS gene mutation rate was 13−22%.…”
Section: Genesmentioning
confidence: 99%
“…As the lesions progress, they may appear more nodular and exhibit erosion of the bone or surrounding structures. Satellite lesions (lesions that surround the initial tumor) also have been reported in many primary oral melanoma lesions [1,4,11].…”
Section: Introductionmentioning
confidence: 99%
“…Primary oral melanoma represents 0.2-8 % of all melanomas [1][2][3] and 0.5 % of all oral cavity malignancies [1,[4][5][6]. The age range varies between 7 and 95 years [7] and typically is diagnosed in the 5th through 7th decades of life [1,3].…”
Section: Introductionmentioning
confidence: 99%